The Effect of Taxpayer Awareness, Tax Sanctions, Moral Obligation, Tax Socialization, and The Drive-Thru SAMSAT System Toward Taxpayer Compliance in Paying Motor Vehicle Tax (Case Study at SAMSAT Badung Bali) - I Putu Edy Arizona; Made Laksmi Sena Hartini; Ni Putu Novita Eka Yanti (AIBPM Publisher, 2023)
Data on motor vehicle tax arrears at the Badung SAMSAT for 2017-2021 has increased, this shown that there are still citizens who don't comply with their assess commitments. The goal of this study was to ascertain how the drive-through samsat system, tax penalties, moral obligation, and tax socialization affected taxpayer compliance with paying motor vehicle taxes at SAMSAT Badung. This study aims to test and obtain empirical evidence of the effect of taxpayer awareness, tax sanctions, moral obligation, tax socialization, and the drive-thru SAMSAT system on taxpayer compliance in paying motor vehicle taxes at SAMSAT Badung. This study uses a survey method with a questionnaire instrument to collect data. The number of samples used is 100 respondents with the sampling method is accidental sampling. The research data were analyzed using multiple linear regression. The results showed that tax socialization and the drive-thru SAMSAT system had a positive impact on taxpayer compliance in paying motor vehicle taxes at SAMSAT Badung. While moral obligation, tax penalties, and taxpayer awareness have no bearing on a taxpayer's willingness to pay motor vehicle taxes at SAMSAT Badung.